ANALYSIS OF INTERNAL, EXTERNAL FACTORS, ACADEMIC PROCRASTINATION IN COMPLETING FINAL ASSIGNMENTS IN COLLEGE STUDENTS - Monal; Marniati; Ihsan Murdani; Maiza Duana; Mardi Fadillah (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Academic procrastination is a delaying behavior often found among students. The study was conducted because there were still a number of students in the 2020 batch of public health study programs who were not on time in completing their studies, allegedly related to procrastination behavior. This study aims to reveal the internal and external factors that trigger procrastination in completing the final project. The method used was descriptive qualitative, informants were selected purposively, namely: one key informant (caprodi), four main informants (students), and three supporting informants (academic supervisors). Data obtained through initial surveys, interviews, and documentation were analyzed through the stages of reduction, data presentation, and conclusion drawing. The results show that the more dominant (internal) factors include weak time management, low self- efficacy, and psychological conditions. While (external) factors including environmental conditions, and social support do not directly cause procrastination but can strengthen or reduce the causes in terms of internal factors. Academic procrastination in 2020 batch students of public health study programs is triggered by a combination of internal and external factors, which are dominated by internal factors. Suggestions, for students it is important to improve time management skills and build self-efficacy through structured and consistent study planning, especially when in the progress of preparing the final project.